ANALYSIS OF PHYSICS LEARNING INSTRUMENTS BASED PROBLEM BASED LEARNING MODEL - Rizka Hasmi Nasution; Sahyar .; Ridwan A Sani (Jurnal Pendidikan Fisika, 2016)
This study aims to produce a device design appropriate learning with problem-based learning model and analyze whether learning instrument developed can improve student learning outcomes. This development research done on a limited test by using a class by using research methods 4D development. 4D method is used as a method for designing a learning device to the stages define, design, and develope, while disseminate not done for a limited test. The development of learning instrument assessed by a team of experts, small group, and then the field test. Improved learning outcomes using the NGain. The result of the design of the learning device developed by researchers in accordance with input from a team of experts, small groups and field testing of the categories eligible to use. There is an increase in student learning outcomes after using problem-based learning instrument with the N-Gain in the medium category.